Extraction of hydroxyapatite and collagen from the Vietnamese tilapia scales. Issue 2 (21st April 2019) - Chinh, Nguyen Thuy; Manh, Vu Quoc; Trung, Vu Quoc; Trang, Tran Do Mai; Hoang, Thai
Abstract: This study reports the suitable condition to extract hydroxyapatite (HAp) and collagen from tilapia scales in North Viet Nam. The tilapia scales were treated by Ca(OH)2 5 % solution for 24 hours to remove protein, fat and impurities. The protein‐free scales were continuously sunk in mixture acid solutions to remove minerals. The HAp was obtained from this solution by precipitating with 0.5 M NaOH. The mineral‐free scales were immersed in 0.5 M CH3 COOH solution and precipitated collagen was obtained by adding of 0.5 M NaCl solution. The methods including Energy dispersive X‐ray diffraction (EDX), Fourier transform infrared spectroscopy (FTIR), Field emission scanning electron microscopy (FESEM) were used to determine characteristics, structure and morphology of HAp and collagen. The HAp was dried at 150°C for removing water and some organic substances and then, washed repeatedly by distilled water to obtain high purity HAp, size of 30‐40 nm, and Ca/P ratio = 1.70, closed to Ca/P ratio = 1.67 in bones and human teeth. The collagen was obtained in raw form, contains C, N, O, S, Na, Cl atoms in structure.